The influence of personality traits on moral disengagement and drug use among adolescents with discipline problems - Mohamed, Noor Hassline; Beckstein, Amoneeta; Rathakrishnan, Balan; Pang, Nicholas Tze Ping (Jurnal Cakrawala Pendidikan, 2022)
This study aimed to assess the influence of the Big Five personality traits, namely openness, conscientiousness, extraversion, agreeableness, and neuroticism on an individual inclination to moral disengagement and drug use. A total of 132 fourteen to seventeen-year-old adolescents with discipline problems from the secondary schools in Selangor, Malaysia was involved in the study. Employing correlational designs, the data were collected by using standardised questionnaires including the Moral Disengagement Scale, the Big Five Inventory, and the Drug Abuse Screening Test. The results showed that personality traits had a strong relationship with moral disengagement and drug use. More precisely, the study discovered a positive correlation between neuroticism and moral disengagement and drug use. Furthermore, the findings revealed that moral disengagement had an indirect effect on drug use through neuroticism, which served as a mediator between the two variables studied. The findings suggested that neuroticism was a personality trait associated with moral disengagement and drug use in adolescents who struggled with discipline problems. These factors have implications for school counselling and drug treatment and prevention programmes. Further recommendations and future research on this topic have been suggested in this article.